Comparison of the efficacy of laparoscopic primary closure of the common bile duct and T-tube drainage in the treatment of choledocholithiasis in elderly patients - Xiaofan Hua; Gang Wang; Bin Li; Genhai Shen; Wei Liu (BMC Geriatrics)
Abstract Background With the aging population, the incidence of choledocholithiasis in elderly patients is increasing. Since interventional endoscopy cannot address gallbladder stones, laparoscopic common bile duct exploration is more suitable for elderly patients. However, there is still controversy over whether primary suture of the common bile duct or T-tube drainage is more appropriate for elderly patients. This study aims to explore the clinical efficacy of these two methods in treating elderly patients (≥ 70 years) with choledocholithiasis, comparing their surgical safety, complication rates, postoperative recovery, and long-term outcomes. Methods A retrospective analysis was conducted on 97 patients diagnosed with choledocholithiasis (or combined with gallbladder stones), aged 70 years or older, and who underwent laparoscopic primary suture of the common bile duct (PC group, 45 cases) or T-tube drainage (TD group, 52 cases) in our hospital from January 1, 2022, to October 30, 2023. The preoperative characteristics, intraoperative outcomes, and postoperative recovery of the PC and TD groups were compared. Results The PC group had shorter operative time, common bile duct suture time, bowel function recovery time, 6-day postoperative VAS, total hospital stay, and postoperative hospital stay compared to the TD group. There was no significant difference in postoperative complications between the two groups, with both experiencing cases of pulmonary infection (PC: 3 cases, TD: 2 cases), cardiovascular events (PC: 2 cases, TD: 1 case), and bile leakage (PC: 3 cases, TD: 4 cases). Additionally, the TD group had 3 cases of T-tube site wound infection, 3 cases of acute cholangitis, and 2 cases of readmission within 30 days post-discharge. After a median follow-up of 16 months, no residual or recurrent stones or biliary duct strictures were observed in either group. Conclusion Laparoscopic primary suture of the common bile duct avoids some complications associated with T-tube drainage and offers advantages such as less trauma, faster recovery, and shorter hospital stay. For elderly patients with clear indications, this surgical method is a safe and feasible option.